Quality improvement on mechanical properties of FDM 3D printed triply periodic minimal surfaces (TPMS) structure for tissue engineering scaffold / Nor Hasrul Akhmal Ngadiman ... [et al.] - Ngadiman, Nor Hasrul Akhmal; Mustafa, Nur Syahirah; Omar Alkaff, Ahmed Ali; Mat Saman, Muhammad Zameri (UiTM Press, 2024)
Bone tissue engineering is the best alternative to treat large-scale bone defects by developing a scaffold. Many attempts have been made, but mechanical properties are still a significant concern in producing a feasible scaffold. This study aims to optimize the parameters of Fused Deposition Modeling (FDM) 3D printing, specifically layer thickness, flow rate, filling density, and filling pattern. The objective was to improve the compressive strength and Young's modulus of the scaffolds, which are crucial for the effective regeneration of bone tissue. Through this study, it has been found that the significant parameters to develop a feasible scaffold are layer thickness, flow rate, and filling density. By optimizing the parameters to a layer thickness of 0.05 mm, a flow rate of 50%, and a filling density of 100%, the resulting scaffolds exhibited a compressive strength of 0.8329 MPa and a Young's modulus of 16.42 MPa. These values exhibit extraordinary mechanical durability. The study's importance lies in its contribution to advancing more efficient bone scaffolds. These tailored scaffolds, which balance mechanical strength and biological functions, can potentially enhance bone repair and regeneration. This study establishes a foundation to produce more dependable and effective scaffolds, ultimately improving bone regeneration treatments.